Delayed Surgical Treatment of a CE1 Lung Cyst Resulting in Pericystectomy of CE4 Cyst - Gian Luca D’Alessandro; Agostina Pontarelli; Armanda Leka; Dino Casazza; Raffaella Lissandrin; Tommaso Manciulli; Annarita Botta; Roberto Parrella; Enrico Brunetti; Pietro Rinaldi (Case Reports in Infectious Diseases)
Lung is the second most common locationof cystic echinococcosis (CE), after the liver. Diagnosis of lung CE is often incidental, and clinical manifestations depend on the location and size of the cyst, the most common being chest pain, shortness of breath, expectoration of fragments of endocyst, and haemoptysis. Surgery is the primary treatment, with a minor role for medical therapy. Delayed diagnosis and treatment may have important consequences. We present a case of lung CE in whichsurgical treatment was delayed due to the first wave of COVID-19. Since surgery could not be performed immediately, the patient was kept on albendazole and the cyst stage moved from CE1 to CE3a, to CE4, eventually requiring a more aggressive pericystectomy instead of the commonly performed endocystectomy. The clinical and imaging characteristics of a rare CE4 cyst of the lung are reported.